Non-Test Evaluation Techniques in Islamic Religious Education Learning - Andri Irawan; Bambang Samsul Arifin; Mulyawan Safwandy Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The writing of this article aims to reveal and analyze the importance of implementing non-test evaluation techniques in learning Islamic religious education in order to provide a more real and objective evaluation. The research method used in this writing uses a literature review by attempting to examine and analyze various references in the form of journal articles and the like theoretically. Data collection techniques are processed and analyzed in order to become a clear concept and scientific development. This study concludes (1) The concept of non-test type evaluation is a series of techniques in learning evaluation to measure the psychomotor and affective aspects of students; (2) Non-test evaluation techniques in Islamic religious education learning consist of four, namely observation, interviews, projects and portfolios which are the result of selection from other non-test techniques as a simplification effort to have a positive impact on the quality of learning evaluation; and (3) Techniques in evaluating Islamic religious education learning still have problems to be applied, but in the current era of artificial intelligence or AI-based technology development there is no reason for teachers not to answer these challenges. AI can be used as a tool in alleviating problems in evaluation.